Drying of Malaysian Capsicum annuum L. (Red Chili) Dried by Open and Solar Drying - Ahmad Fudholi; Mohd Yusof Othman; Mohd Hafidz Ruslan; Kamaruzzaman Sopian (International Journal of Photoenergy)
This study evaluated the performance of solar drying in the Malaysian red chili (Capsicum annuum L.). Red chilies were dried down from approximately 80% (wb) to 10% (wb) moisture content within 33 h. The drying process was conducted during the day, and it was compared with 65 h of open sun drying. Solar drying yielded a 49% saving in drying time compared with open sun drying. At the average solar radiation of 420 W/m2 and air flow rate of 0.07 kg/s, the collector, drying system, and pickup demonstrated efficiency rates of approximately 28%, 13%, and 45%, respectively. Evaporative capacity ranged from 0.13 to 2.36 kg/h, with an average of 0.97 kg/h. The specific moisture extraction rate (SMER) of 0.19 kg/kWh was obtained. Moreover, the drying kinetics of C. annuum L. were investigated. A nonlinear regression procedure was used to fit three drying models. These models were compared with experimental data on red chilies dried by open sun drying and those dried by solar drying. The fit quality of the models was evaluated using their coefficient of determination (R2), mean bias error, and root-mean-square error values. The Page model resulted in the highest R2 and the lowest mean bias and root-mean-square errors.